Peptide Synthesis in Aqueous Solution With a Reusable Solid Phase - Yong, Ma (Journal of Peptides, 2024)
A procedure has been developed for synthesizing peptides in an aqueous solution with a reusable solid phase. Specifically designed linker molecule is employed to attach peptides to hydrophilic solid phases, enabling Solid Phase Peptide Synthesis (SPPS) in aqueous solutions. The linker molecule is utilized to connect peptides to an anionic exchange resin during peptide synthesis in an aqueous solution. The general structure of the linker molecule is Fmoc-AA-CH2-Ph-Rx-SO3-, the Fmoc (9-fluorenylmethoxycarbonyl) group serves as a protecting group for amino acids. Amino acids (AA) are linked to the solid phase through a structure of Methoxyphenylcarbonyl group, which is cleavable under strong acidic conditions. The sulfate group is present for forming an ionic bond with the solid resin in an aqueous solution. In this procedure, Fmoc-AA are utilized as building blocks for sequentially adding amino acids in peptide synthesis. Due to Fmoc-AA poor solubility in aqueous solutions, a procedure was developed to enhance the solubility of hydrophobic compounds, with a specific emphasis on dissolving Fmoc-protected Amino Acids (Fmoc-AA) in an aqueous solution. This enhancement facilitates SPPS in aqueous conditions with Fmoc-AA as building blocks. Cationic exchange resin, which is reusable, serves as the solid phase. Our research objective is to shift from the use of organic solvents to an aqueous system while maintaining the existing SPPS practices in organic solvents as closely as possible. This transition involves minimal alterations, maintaining consistency with the organic solvent system, except for the utilization of novel peptide linker molecule to hydrophilic solid resins that are commercially available. This approach is designed to facilitate a more readily acceptable transition for the peptide synthesis industry from using organic solvents to aqueous solution, contributing to greener and more sustainable synthetic methodologies.
Keywords: Solid-phase peptide synthesis (SPPS); SPPS in aqueous solution; greener SPPS